Linguistic and communicational analysis on energy concepts in Europe 2014 - Kovtyk, Bogdan (Glottodidactica, 2015)
The article is concentrated on the topics of linguistic and communicational analysis of near future energies among concepts of renewable energy sources in Europe 2014 based on visions according to Project Europe 2030. The analysis will be realized on the basis of text corpus of ZEIT.ONLINE and proved by the socio-empiric method SYMLOG as linguistic and communication research tool for systemic multilevel observation of groups dealing with the discourse of new energies. The article will show the various ways and debates within new linguistic and communicational analysis of the energy sources in the EU in general and as comparison between single EUstates including Germany and Poland.